Cultural Legacy in Luci Tapahonso's poem: "A Blessing" (مجلة ديالى للبحوث الانسانية, 2025)
This exploration of "A Blessing," a poem by Luci Tapahonso, focuses on its thematic significance in relation to cultural legacies. The poem functions as a moving story within Tapahonso's body of work, highlighting the tenacity and commitment needed by marginalized communities to overcome societal exclusion and marginalization. This investigation analyzes the intricate social dynamics and identity struggles encountered by Native Americans in comparison to the larger American culture. The poem comes through as an effective representation of Tapahonso's own ethnic identity and a recognition of the constancy required to overcome the challenges faced by disadvantaged populations. The research also emphasizes that Tapahonso's thematic exploration encompasses expressions of appreciation for the support and assistance provided by her people, highlighting the transforming power of identifying and helping individuals who have faced social isolation. In the end, "A Blessing" rings true as a monument to the ongoing cultural legacy of Native Americans and a plea to promote a more welcoming and equal society by honoring both individual success and group resiliency